The Relationship of Quality Control, Total Quality Management on MSMEs Performance - Septa S, Suherdian; Rahmadia R, Wahyu; Rahayu, Witri; Lusiana, Lusiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
The study aims to discover the effect of quality control and total quality management (TQM) on MSMEs Performance. The unit of analysis is Micro, Small and Medium Enterprises (MSMEs) in Padang City. The study utilized primary data which is obtained through the questionnaire. Sampling technique by using quota sampling. 100 questionnaires from MSMEs were returned as a final sample. Data were analyzed using multiple regression analysis performed by SPSS software. The result shows that quality control positively and significantly affects organizational performance. Total quality management has a positive and significant effect on organizational performance. MSMEs can adopt simple yet effective quality control practices to reduce production defects and waste. Quality control processes integrated with TQM enable MSMEs to identify quality issues at every production stage, making operations more efficient.